Organic Waste Innovative Marketing Strategies for Organic Waste Compost through Modern Tebe Manufacturing: Innovative Marketing Strategies for Organic Waste Compost through Modern Tebe Manufacturing - I Wayan Dikse Pancane; I Wayan Suriana; I Nyoman Gede adrama; I Putu Budi Arnaya; I Putu ariawan; I Komang Agus ariana; I Wayan Sugarayasa; Made Asna (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service aims to develop a marketing strategy for compost processed by organic waste by utilizing contemporary tebe making innovations. Through a practical and participatory approach, we implement marketing strategies focused on increasing the attractiveness and added value of compost. The tebe making process integrated with the latest technology takes center stage, creating ecologically and aesthetically superior organic compost products. In this dedication, we interact directly with the community to educate them about the benefits of organic compost and introduce marketing strategies that can increase interest and participation. The results of this service are expected to make a positive contribution to organic waste management in the community, while creating economic opportunities through the marketing of innovative and sustainable compost products. Overall, this project reflects our commitment to delivering sustainable solutions and strengthening community involvement in managing organic waste.